Donor impurity-related intraband optical absorption in a single quantum ring: Hydrostatic pressure and intense laser field effects - Barseghyan, M. G. (European physical journal plus, 2016)
. The simultaneous influence of hydrostatic pressure and intense laser field on hydrogenic donor impurity states and intraband optical absorption has been investigated in GaAs/ Ga 1 - x ˜ Al x ˜ As quantum ring. The one-electron energy spectrum and wave functions have been found using the effective mass approximation and exact diagonalization technique. The intraband absorption coefficient is calculated for different values of the hydrostatic pressure, intense laser field parameter and different locations of hydrogenic donor impurity. The simultaneous influence of hydrostatic pressure and intense laser field shows that while the increment of the first one leads only to the blueshift of the absorption spectrum, the augmentation of the second one makes the redshift. In addition, both blueshift and redshift of the spectrum have been obtained with the changes of impurity location. The obtained theoretical results indicate good controlling means of the optical spectrum of ring-like structures by the combined influence of the considered factors.